The Participation of Civil Society Institutions in Anti-Corruption Policy of Uzbekistan (Global Journal of Human-Social Science, 2022)
Corruption is one of the global problems of our time. The article discusses the problems of the study of corruption and civil society in modern Uzbekistan. The main emphasis in the article is on the lack of a clear definition of the causes of corruption, as well as its relationship with civil society and, as a consequence, the ineffectiveness of methods of struggle. To increase the effectiveness of the fight against corruption at the global level, Uzbekistan needs international cooperation. Currently, there are a number of international organizations that pay sufficient attention to anti-corruption issues. Separately considered are the roles of civil society institutions in the fight against corruption.
Keywords: state; corruption; anti-corruption; anti-corruption measures; civil society; international non-governmental organizations